<span>f(x) = 2x – 5
</span><span>f(22) = 2(22) – 5 = 44 -5 = 39
answer
</span><span>D39</span>
Given the information, you can only write an expression and simplify it:
6(3(x+24))
6(3x+72)
SOlution: 18x+432
I hope I helped you with your solution! If you could give me brainliest, I would be very thankful!
Answer:
x = 3/4 + (3 sqrt(5))/4 or x = 3/4 - (3 sqrt(5))/4
Step-by-step explanation:
Solve for x over the real numbers:
8 x^2 - 12 x - 23 = -5
Divide both sides by 8:
x^2 - (3 x)/2 - 23/8 = -5/8
Add 23/8 to both sides:
x^2 - (3 x)/2 = 9/4
Add 9/16 to both sides:
x^2 - (3 x)/2 + 9/16 = 45/16
Write the left hand side as a square:
(x - 3/4)^2 = 45/16
Take the square root of both sides:
x - 3/4 = (3 sqrt(5))/4 or x - 3/4 = -(3 sqrt(5))/4
Add 3/4 to both sides:
x = 3/4 + (3 sqrt(5))/4 or x - 3/4 = -(3 sqrt(5))/4
Add 3/4 to both sides:
Answer: x = 3/4 + (3 sqrt(5))/4 or x = 3/4 - (3 sqrt(5))/4
Find the area of all the separate figures and add them together
area of rectangle = length x width
11 x 3 = 33 ft
area of square = a^2
3^2 = 9ft
area of triangle = base x height over 2
11 x 3 = 33
33 over 2 = 16.5 ft
33 + 9 + 16.5 = 58.5 ft ^ 2
Answer:
No, its not
Step-by-step explanation:
The points of the image are not moved away from the center of dilation proportionally. I don't think anyway.